HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN SELF – ESTEEM DENGAN RESILIENSI PADA KORBAN TOXIC RELATIONSHIP - Aprilia Kartika Sari; Mochamad Widjanarko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to empirically determine the relationship between social support and self-esteem with resilience in victims of toxic relationships. Resilience is an individual's ability to overcome and adapt to major challenges or problems in life. This includes the ability to survive under pressure and face difficulties or trauma that may be experienced throughout life. This study used a quantitative method with a purposive sampling technique and a total of 101 respondents involved. The measuring instruments used to obtain data were the social support scale, self- esteem scale, and resilience scale. The results of this study showed very significant results p = 0.000 (p <0.01) and a correlation coefficient (r) of 0.612, with an effective contribution of 37.4%. This means that there is a very significant positive relationship between social support and self-esteem with resilience in victims of toxic relationships so that this hypothesis is accepted.